Mechanical and electrical behaviours of polybutylene terephthalate/ polyethylene terephthalate blend nanotube composites - Rajakumar, P.R.; Nanthini, R. (International Journal of Advanced Chemistry, 2013)
Polybutylene Terephthalate (PBT) / Polyethylene Terephthalate (PET) nanotube composite blend was fabricated using melt blending technique in a twin extruder. The blend composition was optimized at PBT-PET weight ratio of 80-20. The effect of incorporation of MWCNT on the mechanical, electrical properties of the nanotube composites blend has been investigated. Mechanical properties show marginal improvement in impact strength, but considerable improvement in tensile strength and flexural strength. Changes in electrical properties observed.